Book in the media systeme - M. G. Vokhrysheva (Библиосфера, 2020)
Book functioning in the modern society, called by the researchers not only as an information but also a media one, has changed. Book and media are considered as unique phenomena the essence of which being reflected in sense-filled notions. The aim of the article is to reveal the place of book in the media space. Its tasks are: 1) on the base of modern home and foreign dictionaries and encyclopedias to show the difference in approaches to definitions and expose the content of the concepts “book” and “media”; 2) to demonstrate the specifics of the book entering into contemporary media sphere both on the level of its transformation into new existence forms in the electronic environment and on the level of its being as an independent unit in the form of a printed book; 3) to establish the possible methodological approaches to the investigation of the problem and suggest the methodology of transdisciplinarity as the basic one. Methods used are: theoretical analysis and generalization, terminological analysis, transdisciplinary approach. The term “media” describes the whole sphere of activity (“media sphere”) in the centre of which are means of information and communication, social institutes, dealing with the content production and delivering it to the public. The book is included into this sphere transforming its form into a new electronic one and getting benefits through the variability ofelectronic resources, virtuality, a new language and communicative formats. A printed book with its great number of valuable properties, first of all ability to influence inner cognitive and psychological perception structures while reading faces significant difficulties in its publishing and dissemination; it’s transferred into the second row of information policy and mass cognition. Thus, it’s methodologically important to consider book in any form as a significant element in the modern media sphere. It’s promising to use the transdisciplinary approach to book research when it is studied not by aspects from the viewpoint of this or that discipline but as a whole using all acquired knowledge.